(3GdYOje GdeKd GdQajY GdbOQs
(3ChdgG (B:s
(3hChd eG PcQJ HYO GSJNGQI Gddg JYGdi QjGVI GdNjd hGdYjhHhGdNUGd hdYH GdQeM s
(3BNQgG (B:s
(3HGH JYdje GdaQS ef ZjQ eSc GdYfGf , hgh Cfc JYed ai HGQcI GddLGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B10s
(3ai GdaQhSjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B34 s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs